Geography teachers' views on textbook use in Portugal: a small scale study in challenging times - Esteves, Maria Helena (2019)
The aim of this research is to analyze Geography teachers’ views on textbook use in the classroom. Recent changes in the Portuguese national curriculum have brought additional demands both to teaching and learning. It was important to understand how textbook use in Geography classrooms is viewed in terms of assisting teachers to manage the new challenges introduced by the national curriculum and its relationship with school Geography. The preliminary results of the research show that textbook use is perceived as very important both for students and teachers, but it is still used in a very traditional way. The existence of new guidelines for teaching and learning present in the national curriculum has not changed the way teachers use textbooks in the classroom. Still, they recognize the need to adapt to the national curriculum guidelines. Some recommendations are presented based on the needs identified by the teachers.